Barriers and Facilitators to Using VR-Based Therapy for Emotional Regulation in Youth with Exceptional Needs - Khadem Fini, Armin; Saadati, Seyed Milad (Psychological Research in Individuals with Exceptional Needs, 2025)
This study aimed to explore the barriers and facilitators influencing the implementation of virtual reality (VR)-based therapy for emotional regulation in youth with exceptional needs. A qualitative research design was employed using semi-structured interviews with 23 purposefully selected participants, including special education teachers, therapists, caregivers, and VR developers, all based in Minnesota, USA. Participants were selected based on their direct involvement with VR therapy programs for youth with neurodevelopmental or emotional regulation challenges. Interviews were conducted until theoretical saturation was reached. Data were transcribed verbatim and analyzed using thematic analysis in NVivo 14, following Braun and Clarke’s six-phase framework. The analysis revealed two main thematic categories: facilitators and barriers. Facilitators included seven subthemes: technological appeal, personalization, therapist control, motivation and engagement, institutional support, caregiver involvement, and observable emotional gains. Barriers were categorized into seven subthemes as well: accessibility and equity issues, sensory limitations, stakeholder resistance, cultural irrelevance, technical difficulties, ethical and privacy concerns, and lack of standardized guidelines. Participants reported that immersive features, real-time therapist adjustments, and family buy-in enhanced VR’s therapeutic effectiveness. Conversely, cost constraints, lack of culturally appropriate content, and technical or ethical challenges hindered adoption. Quotes from stakeholders enriched the thematic interpretation and contextualized the results. VR-based therapy shows promising potential in enhancing emotional regulation among youth with exceptional needs due to its immersive, customizable, and engaging design. However, successful implementation depends on addressing contextual challenges, including accessibility, technical infrastructure, and cultural inclusivity. Stakeholder collaboration and the development of standardized protocols are essential to scale VR interventions in educational and clinical contexts.